2011
DOI: 10.1371/journal.pone.0025707
|View full text |Cite
|
Sign up to set email alerts
|

Humanizing π-Class Glutathione S-Transferase Regulation in a Mouse Model Alters Liver Toxicity in Response to Acetaminophen Overdose

Abstract: BackgroundGlutathione S-transferases (GSTs) metabolize drugs and xenobiotics. Yet despite high protein sequence homology, expression of π-class GSTs, the most abundant of the enzymes, varies significantly between species. In mouse liver, hepatocytes exhibit high mGstp expression, while in human liver, hepatocytes contain little or no hGSTP1 mRNA or hGSTP1 protein. π-class GSTs are known to be critical determinants of liver responses to drugs and toxins: when treated with high doses of acetaminophen, mGstp1/2+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
(49 reference statements)
1
14
0
Order By: Relevance
“…or p.o.) was compared in wild-type, mGstp1/2 null and GSTP1 humanised mice, the humanised mice exhibited a response which was intermediate between those of the wild-type and null mice, consistent with the expression of hGSTP1 in non-parenchymal cell types (Kupffer cells, endothelial cells and bile ducts) but not hepatocytes in the humanised line compared with expression in all (or the majority of) hepatocytes in wild type mice and a complete absence of GSTP in null mice (35). The reporter line we describe will be of utility in the further pursuit of these issues because the construct it contains includes more of the 5′ regulatory region of hGSTP1 and it carries a reporter gene for localisation of hGSTP1 expression as well as the complete coding sequence of hGSTP1 for functional studies.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…or p.o.) was compared in wild-type, mGstp1/2 null and GSTP1 humanised mice, the humanised mice exhibited a response which was intermediate between those of the wild-type and null mice, consistent with the expression of hGSTP1 in non-parenchymal cell types (Kupffer cells, endothelial cells and bile ducts) but not hepatocytes in the humanised line compared with expression in all (or the majority of) hepatocytes in wild type mice and a complete absence of GSTP in null mice (35). The reporter line we describe will be of utility in the further pursuit of these issues because the construct it contains includes more of the 5′ regulatory region of hGSTP1 and it carries a reporter gene for localisation of hGSTP1 expression as well as the complete coding sequence of hGSTP1 for functional studies.…”
Section: Discussionsupporting
confidence: 56%
“…In the livers of hGSTP1::LacZ ROSA26 mice, reporter expression was evident around the portal area and in the epithelium of the gall bladder. This corresponds with the restricted expression of hGSTP1 in human biliary epithelium and gall bladder (34, 35), whereas mGstp1/p2 has been reported to be a major isoenzyme in male mouse liver (36). GSTP1 has previously been reported to be the major GST isoform in human lung (37), being expressed predominantly in the bronchiolar epithelium (38) as observed in the current study.…”
Section: Discussionmentioning
confidence: 87%
“…44 Glutathione-S-transferase (GST) is an enzyme that enables detoxification of NAPQI, as well as other electrophilic substrates (products of xenobiotic metabolism) by binding to GSH. 55 After an initial decline, the GSH level returned or became closer to the normal values depending on the administered dose within the next few hours. In vitro studies suggested that π class GST consumes the majority of GSH for NAPQI detoxication in mice and possibly ameliorates liver injury.…”
Section: Discussionmentioning
confidence: 89%
“…53 Studies in mice showed that the GSH level was decreased by approximately 90 % at 1-and 2-hour intervals after paracetamol treatment. 55 However, the contribution of this enzyme to GSH depletion and liver injury in paracetamol intoxication remains controversial. 54 This is not surprising since the major mechanism involved in early paracetamol hepatotoxicity is inactivation of sulfhydryl groups of various cellular compounds due to NAPQI detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional silencing of GSTP1 gene resulted from aberrant promoter methylation might participant in the development and progression of ACHBLF. Previous studies demonstrated that GSTP1 could defend cells against a wide variety of highly genotoxic and cell‐damaging molecules and played an important role in maintaining cellular vitality and health . Aberrant GSTP1 promoter methylation was associated with loss of GSTP1 gene expression, which might result in the increase in cytotoxic molecules and lead to liver cell damage .…”
Section: Discussionmentioning
confidence: 99%